Talking about the not talked about: use of, and reactions to, a DVD promoting bowel cancer screening to Aboriginal people - Haigh, M.; Shahid, Shaouli; O'Connor, K.; Thompson, S. (Wiley-Blackwell Publishing Asia, 2016)
© 2016 Public Health Association of AustraliaObjective: To examine a) the implementation and use of a DVD developed to educate Aboriginal people about bowel cancer and bowel cancer screening; and b) broader aspects of Aboriginal participation in the National Bowel Cancer Screening Program. Methods: Qualitative methods and descriptive approaches were used. Data were collected using face-to-face and telephone interviews and focus group discussions. There were 67 participants, including those involved in the development and distribution of the DVD, health professionals and Aboriginal community members. Results: Although the DVD received a positive reaction from participants, fewer than half the DVDs had been distributed. Furthermore, the small number of DVDs that had been distributed were under-utilised. Conclusion: The weaknesses do not appear to lie with the resource itself but can be attributed partly to poor distribution and promotion. This may have been compounded by the structure of the National Bowel Cancer Screening Program, which limited the engagement of Aboriginal community members and health providers whose focus is largely directed towards more pressing health care issues. Implications: Interest in the resource may increase once the Aboriginal component of the screening program is more closely linked with primary care.